2008
DOI: 10.1002/glia.20806
|View full text |Cite
|
Sign up to set email alerts
|

17β‐estradiol and progesterone prevent cuprizone provoked demyelination of corpus callosum in male mice

Abstract: Sex hormones, for example, estrogen and progesterone, are thought to affect and delay progression of multiple sclerosis (MS) in pregnant women. Although both steroid hormones are neuroprotective in the brain and elevated during pregnancy, only estrogen was tested in clinical trials. To evaluate the role of 17beta-estradiol (E) and progesterone (P) in prevention demyelination, young adult male mice were fed with cuprizone for a defined time interval and simultaneously treated with steroids by repeated injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(147 citation statements)
references
References 47 publications
(64 reference statements)
7
139
1
Order By: Relevance
“…Preparation of tissues was performed, as previously described (34)(35)(36). For histological and immunohistochemical (IHC) studies, mice were transcardially perfused with 2% paraformaldehyde.…”
Section: Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of tissues was performed, as previously described (34)(35)(36). For histological and immunohistochemical (IHC) studies, mice were transcardially perfused with 2% paraformaldehyde.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…The cuprizone model is a frequently used tool to study regenerative processes in the brain, that is, remyelination (26,35,52,58,59). These studies are many times reported in the context of the demyelinating disorder MS; however, principal mechanisms underlying reappearance of new myelinating oligodendrocytes are most likely relevant for a broad spectrum of diseases in which myelination is disturbed.…”
Section: Significance Of the Study Using The Cuprizone Modelmentioning
confidence: 99%
“…Another issue in elderly women is the increased number of ERa-splice variants, leading to a decline in ERa function (Ishunina & Swaab 2008). Concomitant treatment with other hormones may be protective, for example the use of oestrogen with progesterone (Acs et al 2009). On the other hand, some combination therapies may be counter productive (Irwin et al 2011).…”
Section: Some Caveatsmentioning
confidence: 99%
“…Much less is known about the protective effects of E2 and P4 when coadministered under this paradigm. Both in vitro 31 , and in vivo 32 , E2 and P4 have been recently suggested to attain their fullest protective effect acting in concert. Hence, evaluate whether combined E2 and P4 treatment can protect against brain injury when administered after the ischemic insult is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, combined steroid treatment (E2 and P4) but not the application of single steroids abrogated cell death of cortical neurons by stroke-like injury in vitro 31 . Also, the combined treatment with both steroids but not the individual application of E2 and P4 counteracted the process of demyelination in an experimental multiple sclerosis animal model 32 ; suggesting both steroids attain their fullest protective effect only in concert. Hence, evaluate whether combined E2 and P4 treatment can protect against brain injury when administered after the ischemic insult is essential.…”
Section: Introductionmentioning
confidence: 94%